EVALUASI IMPLEMENTASI SISTEM LAPORAN KEUANGAN PERUSAHAAN PROPERTI ( Studi kasus pada De’Lavender Town HouseMalang) - yadnya, I Made Gandhesa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aimed to evaluate the implementation of financial reporting systemon property business.By using descriptive research method with case study approach that method is chosen for doing this research.The object of this study is Deâ€™ lavender town house, Malang. The businessitselfusingfinancial reporting system which has some minor weaknesses in general ledger, thus generate an incomplete financial report for the business. The recommendations for the business as a result from the study among others: utilizationof chart account number, using general journal, using general ledger, and generating income statement and balance sheet which will give a complete information to assist the decision-making process and can be used by the business as a requirement in the credit submission to the bank creditor.Â Keywords: financial reporting system, property business.